The effects of spironolactone and metoprolol on QT dispersion in patients with congestive heart failure - Akbulut, M; Karaca, I; Ilkay, E; Özbay, Y; Arslan, N (Medimond S R L, 2001)
We aimed to evaluate the effects of spironolactone and metaprolol on ejection fraction (EF), QT dispersion (QTd) and corrected QTd (QTdc) in ischemic heart failure. A total of 106 NHYA class II-III patients (mean age: 58.4+/-12 year; 46 female) were included in this study. The patients were followed for a total 12 weeks by 3 week periods. As a result, mean echocardiographic EF and NYHA functional capacity improved in all groups (p< 0.05). But, these improvements were not significant between groups (p>0.05). Shortening of QTd and QTdc in group-II and group-III were significant when compared with group-I (p:0.000, p:0.001). Spironolactone and metaprolol shortened mortality predictor QTd and QTdc beside their good effect on EF.
4th International Congress on Coronary Artery Disease -- OCT 21-24, 2001 -- PRAGUE, CZECH REPUBLIC
Keywords: Mortality; Morbidity; Blockade; Therapy; Risk